Local Genius dalam Kepemimpinan Nasional - Efrizal Nasution (Journal of Management, Education and Communication, 2026)
Local genius is understood as the local cultural values that are alive within a community and serve as a source of legitimacy, policy direction, and national leadership style. This study examines the role of local genius in Indonesia’s national leadership practices during three significant periods: the Soekarno era, the Soeharto era, and the post-Reform democratic era. The purpose of this study is to analyze how these values have been integrated, modified, or even diminished in the dynamics of Indonesian politics over time. The method used was a literature review employing a qualitative historical approach. Research findings indicate that during the Soekarno era, local genius manifested itself in a spirit of mutual cooperation and revolutionary nationalism, which were integrated into the concept of national unity and nation-building through guided democracy. During the Suharto era, local ingenuity was institutionalized through political stability and economic development, with an emphasis on social harmony and a culture of compliance. Meanwhile, during the Reform era, local genius became fragmented but continued to manifest itself in the form of decentralization, the strengthening of local wisdom, and community participation in democracy